Novel Approach to Prepare Magnesium and Mg-Al Alloy from Magnesia by Using the Closed Microwave Aluminothermic Method - Teng Zhang; Miao Wang; Libin Niu; Jumei Zhang; Huihui Zhang; Mengchun Zhang (Metals, 2023)
Herein, we report a novel approach to obtaining magnesium and nanocrystal Mg-Al alloy from magnesia using a closed microwave aluminothermic method in order to solve the problems of high energy consumption, high pollution, and low productivity in the process of magnesium and its alloy production. The main idea of the paper is to design a technique for the preparation of magnesium–aluminum alloy during the reduction process of MgO directly under atmospheric pressure. Based on this experimental idea, we have established a closed microwave aluminothermic reduction reactor. The great advantage of the reaction device is that it can make the reaction material heat up quickly to the reaction temperature in the microwave heating process and produce high-pressure magnesium vapor, which reacts with aluminum dramatically to form Mg-Al alloy under microwave irradiation. By the calculation of the electromagnetic field of the reaction device and sample using ANSYS electronics desktop 2018, the optimum microwave heating conditions for samples have been established. Based on the calculation results, we demonstrate that magnesium and its alloy are prepared successfully by using this method. In addition, the reduction rate of MgO is greatly improved, which is higher up to 79.97 Wt% when the reduction time is 30 min, at 1273 K, and the Mg2Al3 and MgAl alloy is formed during the reduction process as well. Moreover, the formation mechanism of Mg-Al alloy during the reduction process under microwave irradiation was discussed further. Our findings could provide a new approach, insights, and research directions to obtain magnesium and Mg-Al alloy directly from magnesia under normal pressure.